Pengaruh Pemberian Pakan Komplit Dengan Level Silase Campuran Shorgum dan Daun Gamal dan Konsentrat yang Berbeda Terhadap Konsumsi, Kecernaan BETN dan Energi Ternak Kambing Lokal Betina - Hamanay, Umbu Maaya Limu; Manu, Arnold; Maranatha, Grace (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aims to determine the effect of complete feed with silage levels of a mixture of sorghum and gamal leaves and different concentrates on consumption the digestibility of nitrogen free extract (NFE) and energy of local goats. In this study, 4 local ewes aged 6-8 months were used with a body weight range of 11-15 kg with an average of 12.88 kg and a coefficient of variation of 6.74%. The method used is the Latin Square Design method with 4 treatments and 4 periods as replications. The treatment in this study was P0 = 80% silage + 20% concentrate, P1 = 70% silage + 30% concentrate, P2 = 60% silage + 40% concentrate and P3 = 50% silage + 50% concentrate. The parameters studied in this study were the consumption and digestibility of NFE and energy. The results showed that consumption of NFE P0 227.21 g/e/h, P1 243.82 g/e/h, P2 207.80 g/e/h, P3 197.99 g/e/h; digestibility of NFE P0 71.95%, P1 78.36%, P2 76.49%, P3 72.60%; energy consumption P0 2009.08 kkal/e/h, P1 2149.27 kkal/e/h, P2 1854.84 kkal/e/h, P3 1760.87 kkal/e/h and energy digestibility P0 66.03%, P1 70.93%, P2 67.99%, P3 64.01%. The results of analysis of variance showed that treatment had no significant effect (P>0.05) on the consumption and digestibility of NFE and energy. The conclusion of this study was that the provision of complete feed based on a mixture of sorghum and gamal leaf silage at different levels had no significant effect on the consumption and digestibility of NFE and the energy of local ewes.